Sodium bicarbonate improves sprint performance in endurance cycling - Dalle, S.; Koppo, K.; Hespel, P. (Journal of Science and Medicine in Sport, 2021)
Objectives: Oral sodium bicarbonate intake (NaHCO3) may improve performance in short maximal exercise by inducing metabolic alkalosis. However, it remains unknown whether NaHCO3 also enhances all-out performance at the end of an endurance competition. Therefore, the present study investigated the effect of stacked NaHCO3 loading on sprint performance following a 3-h simulated cycling race. Design: Double-blind randomized placebo-controlled cross-over study. Methods: Eleven trained male cyclists (22.3 (18.3-25.3) year; 73.0 (61.5-88) kg; VO2max: 63.7 (57-72) ml kg-1 min-1) ingested either 300 mg kg-1 body weight NaHCO3 (BIC) or NaCl (PL). NaHCO3 or NaCl was supplemented prior to (150 mg kg-1) and during (150 mg kg-1) a 3-h simulated cycling race with a 90-s all-out sprint (90S) at the end. Capillary blood samples were collected for determination of blood pH, lactate and HCO3- concentrations. Analysis of variance (lactate, pH, HCO3-) and paired t-test (power) were applied to compare variables across condition (and time). Results: NaHCO3 intake improved mean power during 90S by ~3% (541 ± 59 W vs. 524 ± 57 W in PL, p = 0.047, Cohen`s D = 0.28, medium). Peak blood lactate concentration and heart rate at the end of 90S were higher (p < 0.05) in BIC (16.2 ± 4.1 mmol l 1, 184 ± 7 bpm) than in PL (12.4 ± 4.2 mmol l-1, 181 ± 5 bpm). NaHCO3 ingestion increased blood [HCO3-] (31.5 ± 1.3 vs. 24.4 ± 1.5 mmol l-1 in PL, p < 0.001) and blood pH (7.50 ± 0.01 vs. 7.41 ± 0.03 in PL, p < 0.05) prior to 90S. Conclusions: NaHCO3 supplementation prior and during endurance exercise improves short all-out exercise performance at the end of the event. Therefore, sodium bicarbonate intake can be applied as a strategy to increase success rate in endurance competitions.